Endoscopic Ultrasound-Guided Hepaticogastrostomy in Malignant Biliary Obstruction: A Comprehensive Review on Technical Tips and Clinical Outcomes - Stefano Mazza; Graziella Masciangelo; Aurelio Mauro; Davide Scalvini; Francesca Torello Viera; Marco Bardone; Letizia Veronese; Laura Rovedatti; Simona Agazzi; Elena Strada; Lodovica Pozzi; Chiara Barteselli; et al. (Diagnostics)
Endoscopic ultrasound-guided biliary drainage (EUS-BD) has dramatically spread and improved in the last two decades and is changing the paradigm of drainage in case of malignant biliary obstruction (MBO). EUS-BD can be achieved from different routes, including the common bile duct (choledochoduodenostomy), intrahepatic bile ducts (hepaticogastrostomy), and gallbladder as a rescue (cholecystogastrostomy/cholecystoduodenostomy). EUS-guided hepaticogastrostomy (EUS-HGS) is a valuable option for biliary drainage in MBO when ERCP fails or is not feasible. EUS-HGS has demonstrated high efficacy with a good rate of technical and clinical success. The safety profile is also overall favorable, although severe adverse events may occur in a significant proportion of patients. From a technical perspective, EUS-HGS is considered one of the most demanding procedures in biliopancreatic endoscopy, requiring multiple steps and high technical skills and experience. In this comprehensive review, technical tips and clinical outcomes of EUS-HGS are reviewed according to the latest evidence in the literature.